Pendekatan Socio-Cultural dalam Pelaksanaan Vaksinasi Covid-19 di Indonesia: Socio-Cultural Approach in the Implementation of Covid-19 Vaccination in Indonesia - Fauzia, Ana; Hamdani, Fathul (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
One of the causes of the widespread transmission of the Covid-19 virus is that many people are ignorant of health protocols so that the outbreak develops into a national and global pandemic. The public's ignorance of the instructions from the government also arises because of the low level of public trust in the government, especially with the emergence of various problems, one of which is the corruption case within the ministry that ensnared two active ministers of the Advanced Indonesia Cabinet (Kabinet Indonesia Maju). In the context of the implementation of vaccination, the government actually took a coercive approach, namely with the emergence of Presidential Decree no. 14 of 2021 which regulates sanctions for delaying or terminating social guarantee for people who receive vaccines but refuse vaccination. The purpose of this study is to analyze the correlation between the approach taken by the government and the level of people compliance in vaccinating and provide an analysis of the socio-cultural approach in the implementation of the Covid-19 vaccination. The research method used is normative law research using legislation, conceptual, and case approaches. The results of the study indicate that the success of vaccination is very dependent on the approach taken by the government, one of which is a collaborative socio-cultural approach and involving public figure or religious leaders as health agents is very important to do to educate the public about the dangers of Covid-19 and the effectiveness of vaccines.